COMMUNITY EMPOWERMENT THROUGH HYDROPONIC NFT TRAINING IN WAJAK, EAST JAVA - Suci, Khansa Alifa; Setyoaji, Ratih Dewi; Aini, Nurul (Erudio Journal of Educational Innovation, 2025)
This community service activity is aimed to empower residents of Wajak, Malang Regency, through training on hydroponic vegetable cultivation using the Nutrient Film Technique (NFT) system. The program introduced basic hydroponic concepts, the use of AB Mix nutrients, and direct practice in planting pakcoy (Brassica rapa var. chinensis) and lettuce (Lactuca sativa). Thirty-six participants from the PKK (women’s organization) and Karang Taruna (local youth organization) actively participated throughout the activity. They were given pre- and post-training questionnaires, and the post-training results showed an increase in participants’ understanding of hydroponic principles, especially in plant nutrition and maintenance. The program not only enhanced participants’ technical knowledge but also fostered motivation to apply hydroponic cultivation at the household level. This demonstrates that participatory and practical learning methods can effectively support community empowerment and encourage the adoption of sustainable agricultural practices in rural areas. The success of this activity indicates the potential for replicating similar training models in other rural communities. Strengthening local capacity through agricultural innovation can contribute to long-term food security and environmental sustainability. Continuous collaboration between academic institutions and local communities is essential to maintain the sustainability and impact of such empowerment programs. Future initiatives are expected to integrate more advanced technologies and monitoring systems to further enhance the effectiveness of community-based agricultural education.